THE IMPACT OF SOCIAL VALUES, KNOWLEDGE, AND FINANCIAL REWARDS ON THE INTEREST IN PURSUING A CAREER AS A PUBLIC ACCOUNTANT - Sabarina Nalsalita Br. Tarigan; Vinny Stephanie Hidayat (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2026)
The purpose of this study is to examine how social values, knowledge, and financial rewards affect people's interest in becoming public accountants. Students from Maranatha Christian University's accounting undergraduate program make up the research population. The sample size is 35 respondents, and the methodology is explanatory research using a purposeful sampling procedure. Multiple linear regression analysis (T-test) was performed on the data using SPSS. According to the study's findings, interest in pursuing a career as a public accountant is influenced by knowledge and financial rewards, but not by social values.